Síntese, caracterização estrutural e óptica de óxidos de alta entropia de terras raras - Santos, Francielle Oliveira dos (2025)
High entropy oxides are a class of materials that have stood out in recent years for presenting a single-phase solution, composed of five or more elements in equiatomic proportions incorporated into the cationic or anionic subnetwork. On the other hand, garnet-type oxides such as YAG (Y3Al5O12) are widely used as scintillators, active media for lasers and white light-emitting diodes when doped with rare earth ions. The incorporation of other rare earth ions into the site is of great interest due to the change in the luminescent properties of this material. In this work, high entropy oxides with a garnet-like structure were produced in the compositions (Y(1-x)/4Gd(1-x)/4Lu(1 x)/4La(1- x)/4Cex)3Al5O12 and (Y(1-x)/4Gd(1-x)/4Lu(1-x)/4Tb(1-x)/4Cex)3Al5O12 where x = 0,004, 0,01, 0,05, 0,1 and 0,2, via synthesis of polymeric precursors. The study of its structural and optical properties, using photoluminescence and radioluminescence, was carried out. Using X-ray diffraction, it was possible to monitor the evolution of crystalline phases and determine the ideal condition for obtaining materials with a single crystalline phase. The photoluminescence (PL) and radioluminescence (RL) spectra exhibited characteristic bands of Ce3+ and Tb3+, but with direct transfer with the crystalline phases, heat treatment temperature and cerium concentration.